Young Entrepreneurs in Sub-Saharan Africa - Katherine V. Gough; Thilde Langevang (Routledge, 2016)
Young people in sub-Saharan Africa are growing up in rapidly changing social and economic environments which produce high levels of un- and underemployment. Job creation through entrepreneurship is currently being promoted by international organizations, governments and NGOs as a key solution, despite there being a dearth of knowledge about youth entrepreneurship in an African context. This book makes an important contribution by exploring the nature of youth entrepreneurship in Ghana, Uganda and Zambia. It provides new insights into conceptual and methodological discussions of youth entrepreneurship as well as presenting original empirical data. Drawing on quantitative and qualitative research, conducted under the auspices of a collaborative, interdisciplinary and comparative research project, it highlights the opportunities and challenges young people face in setting up and running businesses. Divided into a number of clear sections, each with its own introduction and conclusion, the book considers the nature of youth entrepreneurship at the national level, in both urban and rural areas, in specific sectors - including mobile telephony, mining, handicrafts and tourism - and analyses how key factors, such as microfinance, social capital and entrepreneurship education, affect youth entrepreneurship. New light is shed on the multi-faceted nature of youth entrepreneurship and a convincing case is presented for a more nuanced understanding of the term entrepreneurship and the situation faced by many African youth today. This book will be of interest to a wide range of scholars interested in youth entrepreneurship, including in development studies, business studies, youth studies and geography, as well as to development practitioners and policy makers. The Open Access title has now been added to the Open Access page. http://www.tandfebooks.com/page/openaccess